The Cambridge handbook of law and entrepreneurship in the United States - Smith, D. Gordon, 1962-; Broughman, Brian J.; Hurt, Christine (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Law plays a key role in determining the level of entrepreneurial action in society. Legal rules seek to define property rights, facilitate private ordering, and impose liability for legal wrongs, thereby attempting to establish conditions under which individuals may act. These rules also channel the development of technology, regulate information flows, and determine parameters of competition. Depending on their structure and implementation, legal rules can also discourage individuals from acting. It is thus crucial to determine which legal rules and institutions best enable entrepreneurs, whose core function is to challenge incumbency. This volume assembles legal experts from diverse fields to examine the role of law in facilitating or impeding entrepreneurial action. Contributors explore issues arising in current policy debates, including the incentive effect of legal rules on startup activity; the role of law in promoting or foreclosing market entry; and the effect of entrepreneurial action on legal doctrine.
Introduction / D. Gordon Smith and Brian J. Broughman -- Entrepreneurial Action 10 / D. Gordon Smith and Travis Hunt -- The rise of regulatory affairs in innovative startups / Elizabeth Pollman -- Gauguin, Darwin, and design thinking : a solution to the impasse between innovation and regulation / Alice Armitage -- Between the devil and the SEC / Usha R. Rodrigues -- The politics of entrepreneurial capital-raising / Donald C. Langevoort -- Venture exchange regulation : listing standards, market microstructure, and investor protection / Jeff Schwartz -- Relational contracting and business norms in entrepreneurial finance / Brian J. Broughman -- Biotech strategic alliances in law and entrepreneurship / D. Daniel Sokol -- The entrepreneurial business judgment rule / Andrew Gold -- Entrepreneurial action in family-controlled companies / Benjamin Means -- Entrepreneurship incentives for resource-constrained firms / Susan C. Morse -- Corrupting entrepreneurial action / Joseph W. Yockey -- The spinoff advantage : human capital law and entrepreneurship / Orly Lobel -- Organ entrepreneurs / Kieran Healy and Kimberly D. Krawiec.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Business enterprises -- Law and legislation -- United States -- Congresses; Entrepreneurship -- United States -- Congresses